Impact of different operational definitions on mild cognitive impairment rate and MMSE and MoCA performance in transient ischaemic attack and stroke. - Pendlebury, S; Mariz, J; Bull, L; Mehta, Z; Rothwell, P (2013)
BACKGROUND: Mild cognitive impairment (MCI) is at least as prevalent as dementia after transient ischaemic attack (TIA)/stroke and is increasingly recognised as an important outcome in observational studies and randomised trials. However, there is no consensus on how impairment should be defined, and numerous different criteria exist. Previous studies have shown that different criteria for cognitive impairment impact on prevalence rates in epidemiological studies. However, there are few data on how operational differences within established criteria (e.g. Petersen-MCI) affect measured impairment rates and the performance of short cognitive tests such as the Mini Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA), particularly in cerebrovascular disease. We therefore evaluated the effect of different operational definitions on measured rates of Petersen-MCI and on reliability of short cognitive tests in patients with TIA and stroke. METHODS: Consecutive patients underwent the MMSE, MoCA and neuropsychological battery ≥1 year after TIA or stroke in a population-based study. MCI was defined using the Petersen method and subclassified as single or multiple domain, both with (original) and without (modified) subjective memory impairment. Different cut-offs (>1, >1.5 and >2 standard deviations, SD) on a given test relative to published norms were compared together with use of single versus multiple tests to define domain impairment. RESULTS: 91 non-demented subjects completed neuropsychological testing (mean age ± SD 69.7 ± 11.6 years, 54 male, 49 stroke) at a mean of 3.1 ± 1.9 years after the index event. Rates of cognitive impairment ranged from 14/91 (15%) for MCI-original at >2 SD cut-off to 61/91 (67%) MCI-modified at >1 SD cut-off, and the proportion of MCI that was multiple domain varied, e.g. 24/46 (52%) versus only 5/27 (20%) at 1 versus 2 SD cut-off for MCI-modified. Requirement for subjective memory complaint approximately halved estimates [e.g. 17 (19%) vs. 39 (43%) for MCI at 1.5 SD cut-off, single test definition], whereas use of multiple tests versus a single test to define a cognitive domain had less impact. In general, diagnostic accuracy was higher, and optimal cut-offs lower, on MMSE and MoCA for multiple-domain versus single-domain MCI, but the MoCA appeared superior for detecting MCI-modified, whereas the MMSE performed well in detecting MCI-original. CONCLUSION: Even within established criteria for MCI, differences in operational methodology result in 4-fold variation in MCI estimates. Optimal MMSE and MoCA cut-offs are lower, and reliability more similar, when criteria for MCI are more stringent. Our findings have implications for sample size and adjusted relative risk calculations in randomised trials and for comparisons between studies.